PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BERBASIS E - LEARNING (Studi Deskriptif Penggunaan Aplikasi Edmodo di SMA Labschool UPI) - Waode Dhia Nabillah, - (2021)
This research is motivated by a lack of understanding of Islamic religious education teachers in online-based learning, especially during a pandemic like today. Researchers consider Edmodo as a learning management system that can be easily used in online learning activities in Islamic Religious Education subjects. The purpose of this study was to describe (1) Islamic education teaching materials using Edmodo; (2) the pattern of evaluation of Islamic Religious Education using Edmodo; (3) Interactive communication in the Islamic Religious Education class using Edmodo. This study uses a qualitative approach with the Descriptive method. Data collection was carried out by interview, documentation study, and observation. This research was conducted at UPI Laboratory Senior High School, located in Bandung, with research subjects namely students and Edmodo users. The results of the research (1) teaching materials for Islamic Religious Education using Edmodo include synchronous online learning with integrated video conferencing in Edmodo classes and asynchronous using the post feature in Edmodo; (2) The evaluation pattern of Islamic Religious Education using Edmodo uses the Quiz feature for assessment, enrichment, and remedial; (3) Interactive communication using Edmodo utilizes chat and comment features as well as small groups features for communication that is more focused on specific study groups. Keywords: Islamic Religious Education, Edmodo, Online Learning